Hell is a city - Guest, Val 1911-2006; Baker, Stanley 1928-1976; Crawford, John 1920-2010; Pleasence, Donald 1919-1995; Audley, Maxine 1923-1992 (Studiocanal, 2012)
"A 1960's Hammer films production, Hell is a city is a taut, fast-paced thriller set against the grimy back streets and rain-streaked bright lights of Manchester. Stanley Baker stars as a tough, dedicated police inspector on the trail of a man on the run - a man who he had put away for 14 years for robbery - and who will now be sent to the gallows for murder! Clubbing a warder to death as he broke out of jail, the inspector knows now he'll stop at nothing..."
Bildformat: 2.35:1
Original 1960
Special feature: alternate ending
Verlagsnummer OPTD2376
Keywords: Film; DVD-Video